HYDROELECTRIC DAMS: FINANCIAL MANAGEMENT AND AGRICULTURAL USE OF BIOMATERIALS: POTENTIAL OF CALCIUM CARBONATE (CACO₃) FROM THE GOLDEN MUSSEL LIMNOPERNA FORTUNEI IN NEUTRALIZING SOIL ACIDITY (Editora Impacto Científico, 2025)
Efficient dam management faces significant challenges due to the invasion of Limnoperna fortunei, the Golden Mussel, whose biofouling compromises hydraulic structures and increases operational costs in hydroelectric systems. The removal of this mollusk produces large volumes of shells — a residue rich in calcium carbonate (CaCO₃) — with largely untapped reuse potential. This study proposes integrating dam waste management with the agricultural use of biomaterials, assessing the CaCO₃ from L. fortunei shells as a soil acidity neutralizer. Laboratory tests with increasing doses of the material demonstrated pH elevation and acidity reduction, confirming its effectiveness as a liming agent. Utilizing this residue establishes a circular economy model, turning an environmental liability from dam operations into a sustainable input for agriculture and supporting sustainability in dam management.DOI: https://doi.org/10.56238/edimpacto2025.090-040